2010
DOI: 10.5194/bg-7-1-2010
|View full text |Cite
|
Sign up to set email alerts
|

Increase in water column denitrification during the last deglaciation: the influence of oxygen demand in the eastern equatorial Pacific

Abstract: Abstract.Here we present organic export production and nitrogen isotope results spanning the last 30

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…The low glacial Mn/Ca ratios in U. peregrina are consistent with high productivity estimates of Klinkhammer et al (2009), implying that the Mn escaped to the water column, which is in line with the TROXCHEM 3 model. For the same core Martinez and Robinson (2010) showed that at the time of the peak in the Mn/Ca ratios measured in U.…”
Section: The Proxy Value Of Mn/ca Rations In Benthic Foraminifera Andmentioning
confidence: 90%
“…The low glacial Mn/Ca ratios in U. peregrina are consistent with high productivity estimates of Klinkhammer et al (2009), implying that the Mn escaped to the water column, which is in line with the TROXCHEM 3 model. For the same core Martinez and Robinson (2010) showed that at the time of the peak in the Mn/Ca ratios measured in U.…”
Section: The Proxy Value Of Mn/ca Rations In Benthic Foraminifera Andmentioning
confidence: 90%
“…It is based on the correlation of the alkenone SSTs between Site 1239 and the well-dated record at Site 846 (Lawrence et al, 2006). In addition, the age model for two specific intervals, ∼ 3.2-2.7 and ∼ 0.5-0 Ma, is based on δ 18 O and δ 13 C measured on benthic Foraminifera (Rincon- Martinez et al, 2010;Steph et al, 2009) and tuned to the LR04 δ 18 O benthic stack (Lisiecki and Raymo, 2005). Stratigraphy at Site 1240 is also constrained by 14 C dating from planktonic foraminifera for the last 40 kyr and tuned to oxygen isotopes with the LR04 δ 18 O (Lisiecki and Raymo, 2005) between ∼ 2.6-1.8 and ∼ 0.25-0 Myr (Pena et al, 2008;I.…”
Section: Methodsmentioning
confidence: 99%
“…Regional upwelling intensity plays an important role in regulating export production as it controls the nutrient supply to the photic zone. Sedimentary δ 15 N values provide integrated information about regional nutrient (mostly nitrate) dynamics in the EEP (e.g., Farrell et al, 1995;Martinez and Robinson, 2010;Robinson et al, 2009). During microbial transformations, including the uptake and assimilation of nitrate as well as bacterial denitrification, 14 N-bearing nitrate reacts faster so that the remaining nitrate pool becomes enriched in 15 N-bearing nitrate (Altabet and François, 1994).…”
Section: Nutrient and Upwelling Control On Eep Export Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…1a), and is strongly influenced by both high-and low-latitude biogeochemical processes. The eastern tropical South Pacific houses a large region of water-column denitrification that accounts for approximately 15% of the total N removal from the ocean and distributes 15 N-enriched water toward the south and west in the Pacific (Martinez et al, 2006;Robinson et al, 2007;Kienast et al, 2008;Robinson et al, 2009;Martinez and Robinson, 2010) while less 15 N-enriched surface waters are advected from the Southern Ocean (Fig. 1c).…”
Section: Introductionmentioning
confidence: 99%